Development Of Teaching Materials Electronic Module (E-Module) Based On Android The Subject Of Matriks - Chika Dian Tanesari; Maman Fathurrohman; Novaliyosi Novaliyosi (Wilangan: Jurnal Inovasi dan Riset Pendidikan Matematika, 2020)
The use of the module can help overcome misconception and can help students learn to independently. With the advent of the technology, A printed book slowly eleminated because all the information can be acquired by a smartphone. Resulting in reading interest students declining. It is therefore, needed material of teaching interactive module with easly language undersanable students and packed in the pack interesting, So as to attract students interest in reading. Interactive module will be made based on the android to join the habit of students who obtain information use android. This research aimed at producing and develop materials of teaching electronic module based on the android subject of matriks. The research method used is Research and Development (RnD) that involved seven steps: 1) Need Analysis, 2) Researcher as Developer Capability, 3) Product to be Developed, 4) Concept of the Product, 5) Development of the Product, 6)Experts Judgements, 7) Field Testing in Natural Setting Environment. Expert judgements has been done by Technology Experts, Mathematical Education Experts, and Mathematics Experts, has showed that electronic module is receivable to be tested to the student MAN 2 Cilegon who have studied matriks. Field testing is done by the 15 student got the percentage rating 82,28%. From the result of the field testing, the electronic module are in state of very good category based on student’ assessment.